Nursing 2014 drug handbook (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"Emphasizes nursing and safety aspects of drug administration without attempting to replace detailed pharmacology texts. Only the most essential information is included, and helpful graphic symbols, logos, and highlighting draw special attention to critical details that can't be overlooked."